Occult iliac artery stenosis - Criado, Francisco J. (1981)
Assurance of adequate aortoiliac inflow is of paramount importance prior to femoropopliteal reconstruction. Even with the use of arteriography, significant iliac artery stenosis may remain unrecognized. Intraoperative measurement of common femoral artery pressures and exploration of the appropriate iliac system as described here, permits the correction of occult inflow artery lesions and promotes the success of femoropopliteal bypass grafting.